A Reappraisal of Chemotherapy-Induced Liver Injury in Colorectal Liver Metastases before the Era of Antiangiogenics - Eric Nguyen-Khac; Céline Lobry; Denis Chatelain; David Fuks; Jean Paul Joly; Marie Brevet; Blaise Tramier; Charlotte Mouly; Vincent Hautefeuille; Bruno Chauffert; Jean Marc Regimbeau (International Journal of Hepatology)
Background and Aims. Chemotherapy of colorectal liver metastases can induce hepatotoxicity in noncancerous liver. We describe these lesions and assess risk factors and impacts on postresection morbidity and mortality in naive patients to chemotherapy before the era of bevacizumab. Methods. Noncancerous liver tissue lesions were analysed according to tumour, chemotherapy, surgery, and patient characteristics. Results. Fifty patients aged 62 ± 9.3 years were included between 2003 and 2007. Thirty-three (66%) received chemotherapy, with Folfox (58%), Folfiri (21%), LV5FU2 (12%), or Xelox (9%) regimens. Hepatotoxicity consisted of 18 (36%) cases of severe sinusoidal dilatation (SD), 13 (26%) portal fibrosis, 7 (14%) perisinusoidal fibrosis (PSF), 6 (12%) nodular regenerative hyperplasia (NRH), 2 (4%) steatosis >30%, zero steatohepatitis, and 16 (32%) surgical hepatitis. PSF was more frequent after chemotherapy (21% versus 0%, ), especially LV5FU2 (). SD was associated with oxaliplatin (54.5% versus 23.5%, ) and low body mass index (). NRH was associated with oxaliplatin () and extensive resection (). No impact on mortality and morbidity was observed, apart postoperative elevation of bilirubin levels in case of PSF (), longer hospitalization in case of surgical hepatitis (), and greater blood loss in case of portal fibrosis (). Conclusions. Chemotherapy of colorectal liver metastases induces sinusoidal dilatation related to oxaliplatin and perisinusoidal fibrosis related to 5FU, without any impact on postoperative mortality.